Motivating students in learning EFL by using Gamification - Asmi Rusmanayanti; Sirajuddin Kamal; Rizky Amelia (Juliet, 2026)
A teacher has a crucial role in motivating the students, especially in EFL. There should be a way that can make gamification as popular an activity as learning a language nowadays. Many students feel pressure to learn something new or even hard for them, especially in a monotonous way. Therefore, a teacher can create games as a kind of media in EFL teaching and learning activity. Games offer students a fun-filled and relaxing learning atmosphere and encourage, entertain, teach, and promote fluency and communicative skills. This research is descriptive qualitative research that the subjects are 30 students of the Intermediate Speaking Class at the Faculty of Teacher Training and Education at Lambung Mangkurat University. The result shows that there is a positive impact on students' motivation toward some games. They could speak more in a casual atmosphere in the speaking class and have better cooperation among the students during the reading class. The use of games that can motivate the students has been widely accepted as one of the critical factors influencing EFL learning success.